In vitro activity of mecillinam and nitroxoline against Neisseria gonorrhoeae – re-purposing old antibiotics in the multi-drug resistance era. Issue 7 (4th June 2019) - Fuchs, Frieder; Wille, Julia; Hamprecht, Axel; Parcina, Marijo; Lehmann, Clara; Schwarze-Zander, Carolynne; Seifert, Harald; Higgins, Paul G.
Abstract : In 2018, the European Centre for Disease Prevention and Control reported the first cases of extensively drug-resistant Neisseria gonorrhoeae infections in Europe. Seeking new options for antimicrobial therapy we investigated the susceptibility of N. gonorrhoeae to nitroxoline (NIT) and mecillinam (MCM), both of which are currently only indicated to treat uncomplicated urinary tract infections. Clinical N. gonorrhoeae isolates with non-susceptibility to penicillin from two German medical centres were included ( n =27). Most isolates were also non-susceptible to a range of other anti-gonococcal antimicrobials (cefotaxime, ciprofloxacin, azithromycin, tetracycline). All isolates were further characterized by multi-locus sequence typing. MICs of penicillin and cefotaxime were determined by agar gradient diffusion. Production of penicillinase was tested by cefinase disk test. Susceptibility of MCM was investigated by agar dilution, NIT by agar dilution and disk diffusion. Penicillin MICs ranged from 0.125 to 64 mg l −1 and MICs of cefotaxime ranged from < 0.016 to 1 mg l −1 . Five isolates were penicillinase-producers. MICs of MCM ranged from 16 to > 128 mg l −1 whereas MICs of NIT ranged from 0.125 to 2 mg l −1 . NIT disk diffusion (median zone diameter 32 mm) correlated well with results from agar dilution. We demonstrated excellent in vitro activity of NIT against clinical N. gonorrhoeae isolates with non-susceptibility to standard anti-gonococcal antibiotics. MCM activity was unsatisfactory. Correlation of agar dilution and disk diffusion in NIT susceptibility testing is an important aspect with potential clinical implications.